The use and implications of management accounting practices in small and medium-sized enterprises / Zaid Jaradat … [et al.] - Jaradat, Zaid; Taha, Roshaiza; Mat Zin, Rosliza; Wan Zakaria, Wan Zuriati; Abdul Aziz, Rozainun (Universiti Teknologi MARA, 2021)
Management Accounting Practices (MAPs) usage among Small and Medium-sized Enterprises (SMEs) and their implications are examined in this paper. 291 sets of questionnaires were dispersed and six interviews were conducted to gather the data. The usage frequency of individual practices and thematic analysis are deliberated, and the results denote the comparatively low MAPs usage rates among Jordanian SMEs as opposed to those in developed countries. Nonetheless, the reported rates in Jordan are comparable to those in developing countries. Among SMEs, MAPs significantly allow product cost information determination, planning and controlling, and detection of problems. Shortcomings of the traditional system, previous experiments of large companies, and external factors, are considered as the main reasons that motivated SMEs to use MAPs. Insufficient experience, lack of financial resources, and the high costs associated with implementing MAPs are the most crucial reasons that forced SMEs to neglect to use a lot of MAPs. The present study enriches the knowledge of MAPs in the context of SMEs. Also, the significance of MAPs among SME managers is highlighted. Equally, this study should stimulate additional scrutiny and analysis of MAPs amongst SMEs